#TITLE_ALTERNATIVE# - KHAIRUNNISA NOVIAR (NIM : 10212002), ANANDIANI
Graphene oxide is a two-dimensional graphene sheet with oxygen functional groups attached randomly to carbon planes. Graphene oxide (GO) was prepared by dispersing graphite oxide powder in distilled water, which induced GO easy to exfoliate upon ultrasonication. Graphite oxide was prepared by synthesized pristine graphite with modified Hummers method, spesifically substituted ammonium persulfate (APS) for KMnO4 as oxidant agent. GO with different oxidation degree was obtained through variation of oxidant agents, namely APS. GO dispersion were analyzed by Raman Spectroscopy, Photoluminescence Spectroscopy, and UV Ã‚Â– Vis Spectroscopy. Raman spectrum confirmed that graphite have oxidized by strong oxidants. It can be seen from the configuration of defect peak (D-peak) in all GO samples. The ratio intensity of D to G peak were ranging from 0.5 to 0.8. The major ratio intensity of D to G peak emerged in sample B with 3.65 grams of APS, meanwhile the prominent ratio intensity of 2D towards G peak with around 1.02 which indicated single layer graphene was appeared in sample C with 4.5 grams of APS. UV Ã‚Â– Vis investigation was used to determine GO bandgap. GO dispersions exhibit maximum absorption peak at about 260 nm attributable to π⟶π* transition of the atomic C-C bonds. The bandgap of GO was varied from 3.5 to 4 eV. This opening bandgap lead GO to possess much stronger photoluminescence than graphene. GO exhibit main photoluminescence peaks at green emission around 2.2 eV .